THE EFFECTS OF READING HABIT AND SENTENCE PATTERNS MASTERY TOWARDS STUDENTS’ ANECDOTE WRITING SKILL - Fitri Senny Hapsari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The purpose of this research is to know whether there are significant effects of reading habit and sentence patterns mastery towards anecdote writing skill.The research was conducted at SMAN 102 and SMAN 89 of the eleventh grade with total population 345 students and for the sample 70 students that randomly taken. The method used in the research was a survey. Data of Reading Habit, Sentence Patterns Mastery and Anecdote Writing Skill were acquired from the test. The data was analysed using descriptive statistical method, multiple correlation coefficient, determination coefficient, and multiple regression analysis. To test the statistics is used ttest and ftest .Data collective done by giving essay test for anecdot writing skill,30 items of multiplechoice test for Reading Habit, and 10 items essay test for sentence pattern mastery given to class at SMAN 102 and SMAN 89.The result of data analyzes shown there are significant effects of reading habit and sentence patterns mastery towards anecdote writing skill